The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1099/vir.0.015511-0
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of the (nucleoside-2'O)-methyltransferase activity of dengue virus protein NS5 using purified capped RNA oligonucleotides 7MeGpppACn and GpppACn

Abstract: The flavivirus RNA genome contains a conserved cap-1 structure, 7Me GpppA 29OMe G, at the 59 end. Two mRNA cap methyltransferase (MTase) activities involved in the formation of the cap, the (guanine-N7)-and the (nucleoside-29O)-MTases (29O-MTase), reside in a single domain of nonstructural protein NS5 (NS5MTase). This study reports on the biochemical characterization of the 29O-MTase activity of NS5MTase of dengue virus (NS5MTase DV ) using purified, short, capped RNA substrates ( 7Me GpppAC n or GpppAC n ). N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 46 publications
5
32
0
Order By: Relevance
“…The methyl transfer efficiency is similar (Fig. 3B), suggesting that both substrates can be methylated at the 2=-O position of the adenosine ribose, as already reported for DENV and WNV MTases (19,33). Additionally, the ZIKV MTase domain shows an optimal activity between pH 8 and 9 (Fig.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The methyl transfer efficiency is similar (Fig. 3B), suggesting that both substrates can be methylated at the 2=-O position of the adenosine ribose, as already reported for DENV and WNV MTases (19,33). Additionally, the ZIKV MTase domain shows an optimal activity between pH 8 and 9 (Fig.…”
Section: Resultssupporting
confidence: 61%
“…However, it is noteworthy that our biochemical assay might not be optimal to look for a possible interplay between the two domains as the RNA used by the MTase is not neo-synthesized by the RdRp. As observed for its close relatives DENV and WNV, the 2=-O-MTase activity can be detected using different short RNA substrates with no obvious sequence specificity (19,33). In contrast the N-7-MTase activity requires an RNA substrate forming a hairpin structure mimicking the SLA structure conserved among flaviviruses (7,20).…”
Section: Discussionmentioning
confidence: 96%
“…We first determined the impact of mutations affecting the ␣␤NLS on 2=O-MTase activity by measuring the transfer of a 3 Hradiolabeled methyl group contained in S-adenosylmethionine to a 5=-terminal fragment (corresponding to nucleotides 1 to 172) of the DENV-2 RNA genome (35). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Current literature highlights the development of effective nucleoside analogues tested in vitro that target RNA replication by inhibiting incorporation of nucleotides into the newly synthesized RNA strand (Cameron & Castro, 2001;Yin et al, 2009) or targeting the active site of the enzyme such as the S-adenosyl methionine (SAM) pocket of the MTase which is essential for methylation (Selisko et al, 2010). It has also been suggested that targeting interactions of nonstructural proteins in the replication complex is another approach to designing specific antivirals (Loregian et al, 2002).…”
Section: Introductionmentioning
confidence: 99%